PENGARUH UKURAN PERUSAHAAN, SEVERITY, DAN ASSETS RETRENCHMENT TERHADAP KEBERHASILAN CORPORATE TURNAROUND - Fauzia Febrianti; Agung Juliarto (Diponegoro Journal of Accounting, 2022)
This study aims to examine the effect of firm size, severity, and asset retrenchment on the success of corporate turnaround. This study uses resource based theory to analyze this phenomena. The sample in this study is the manufacturing sector companies listed on the Indonesia Stock Exchange in 2015-2020 with a total sample of 80 companies. Sample selected was done by using purposive sampling method with predetermined criteria and requirements. The analytical method used in this study is logistic regression analysis.The results of the study show that firm size and asset retrenchment have a positive and significant impact on corporate turnaround. Meanwhile, severity has a negative but significant impact on corporate turnaround.